Hemostatic Challenges in Pediatric Critical Care Medicine—Hemostatic Balance in VAD - Ghbeis, Muhammad Bakr; Vander Pluym, Christina J.; Thiagarajan, Ravi Ram (Frontiers in Pediatrics, 2021)
Ventricular assist devices (VAD) are increasingly used in children as a bridge to transplantation. Safe and effective anticoagulation is required for successful management of children supported with ventricular assist devices. Developmental hemostasis, device hemocompatibility, plastic to body ratio, surgical variable techniques, lack of knowledge on pharmacokinetics of anticoagulants, and wide variability in anticoagulation protocols have all contributed to increased incidence of bleeding and thromboembolic complications. New collaborative learning networks, such as the ACTION network, provide opportunities to define best practices, optimize and reduce anticoagulation related adverse events. Changes in anticoagulation strategy from the use of heparin to a direct thrombin inhibitor such as bivalirudin have helped reduce bleeding and clotting complications.